Occurrence of Gastro-Intestinal Parasites in Polish Primitive Horses from the Roztocze National Park, Poland - Slivinska, K.; Wrуblewski, Z.; Gawor, J. (Вестник зоологии, 2013)
The study was performed to investigate the gastrointestinal parasite fauna using the method of diagnostic deworming in own modification in 29 Polish primitive horses (Equus caballus) from the Roztocze National Park, south-east of Poland. The parasite community was comprised of 35 species represented by three nematode families (Strongylidae, Ascaridae, Habronematidae), one cestode family (Anoplocephalidae) and larvae of insects from the family Gasterophilidae (Diptera). Strongylidae being 100 % prevalent was represented by 31 species from the subfamily Strongylinae (6 species) and Cyathostominae (25 species). Parascaris equorum was recorded in 48.3 %, Habronema muscae in 55.2 %, tapeworms (Anoplocephala perfoliata) in 24.1 % and Gasterophilus intestinalis larvae in 41.4 % of horses surveyed. The present results showed high prevalence of pathogenic intestinal parasites, which create the risk of health problems for horses living free in the reserve as well as stabled horses, when rarely treated. Обсуждаются результаты исследования желудочно-кишечной паразитофауны у 29 лошадей породы польський коник (Equus сaballus), которые разводятся в условиях вольного и конюшенного содержания в Розточанском национальном парке, что на юго-востоке Польши. При этом был использован метод диагностической дегельминтизации в собственной модификации. Выявлено, что сообщество паразитов состояло из 35 видов, которые были представлены семeйствами Strongylidae, Ascaridae, Habronematidae (Nematoda), Anoplocephalidae (Cestoda) и личинками насекомых из семейства Gasterophilidae (Diptera). Стронгилиды были найдены у всех исследованных лошадей (100 %) и представлены 31 видом из подсемейства Strongylinae (6 видов) и Cyathostominae (25 видов). Parascaris equorum был зафиксирован в 48,3 %, Habronema muscae в 55,2 %, ленточные черви (Anoplocephala perfoliata) в 24,1 % и личинки Gasterophilus intestinalis в 41,4 % исследованных лошадей. Полученные результаты выявили высокую распространенность патогенных кишечных паразитов, которые представляют опасность для здоровья лошадей в условиях вольного и конюшенного содержания, а также в случае нерегулярных антигельминтных обработок поголовья.